Impact of plant growth regulators and nutrients on guava (Psidium guajava) yield in the south-eastern Rajasthan - Devi Darshan; Hitesh, Pindoriya; Dangi, Kamlesh Kumar; Dhawai, Dushyant Singh; Devi, Reema; Singh, Navprem (Current Horticulture, 2025)
The experiment was conducted at Horticulture Research Farm, Career Point University, Kota, during 2023-24 to examine the influence of plant growth regulators and nutrients on fruit setting and physiochemical attributes of guava (Psidium guajava L.) cv. L-49. The plants received first dose of PGRs and nutrients at fruit setting and second at fruit development stage. Foliar application of potassium sulphate (1.0 %) significantly reduced fruit drop (39.77%), while improved fruit setting (71.05%) and fruit retention (60.23%). The foliar application of potassium sulphate (1.0%) increased fruit weight (142.43g), fruit length (8.71cm), fruit width (7.89cm), fruit volume (132.77cc), TSS (11.70%), TSS: acid ratio (30.00), vitamin C (174.10), pectin (1.83 %), reducing sugar (3.80%), non-reducing sugar (3.45%) and total sugars (7.25%) and minimum acidity (0.39%). The foliar application of potassium sulphate (1.0%) also improved the fruiting and physiochemical characteristics of guava cv. L-49 as compared to the control.